Knowledge and Innovation Potential in Inter-organizational Network Cooperation: A Study on Polish Clusters - Beata BARCZAK (Communications of International Proceedings, 2021)
The purpose of this paper is to develop a concept for assessing the knowledge and innovation potential of Polish clusters, as well as to review and critically evaluate research, concepts and approaches to measuring the knowledge and innovation of organizational networks. The research concept is based on a multifaceted approach to the knowledge and innovation potential of clusters. The basic (general) objective of the research is a multi-criteria assessment of the knowledge and innovation potential of clusters, carried out in the field of knowledge management and organizational learning, and in the field of innovation Methods of categorization, scoring and ranking were used for data interpretation and presentation. The method of examining the opinions of experts was also used. The results of the conducted research show that the studied clusters are characterized by an average or satisfactory level of the knowledge and innovation potential index. The results show the evaluation of the degree of use of the knowledge management concept and assessment of the innovation potential in terms of individual criteria. The conducted analyzes enabled the presentation of a research tool with a set of measures enabling the assessment of the knowledge and innovation potential of inter-organizational networks. The presented research method and results may lead to further comparative, dynamic and spatial analyzes and research. In further research, it is also possible to use the analysis of relations within the cluster, and then the analysis of knowledge flow. Originality and value this paper is to present an original method (model) for assessing the potential of knowledge and innovation, indicating the criteria and patterns of assessment. The paper also presents the results of empirical research. On the basis of the research conducted, the implications for both theory and practice have been formulated.
Keywords: Knowledge and Innovation Potential; Organizational Network; Organizational Network Cooperation; Clusters